Analisis Sistem Pengendalian Intern Atas Penerimaan Retribusi Parkir Tepi Jalan Umum Pada Dinas Perhubungan Kota Palembang - Sri Sutandi; Masnoni; Nelly; Irsan; Lia Sari (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2020)
The results showed that the implementation of the internal control system on the performance of the Palembang City Transportation Service was categorized as quite effective, because it was in accordance with Government Regulation Number 60 of 2008 concerning the Government's Internal Control System (SPIP). The implementation of the Internal Control System on the procedure for receiving parking fees at the Palembang City Transportation Service has not been effective because there are no procedures and direct supervision of parking attendants and parking collectors so that they are prone to deviations which indicate that retribution receipts do not reach the target. The implementation of the Internal Control System for the previous year's realization was categorized as quite effective because it was above half of the target. Meanwhile, the realization of the last year experienced a drastic decline below half the target, so it was categorized as ineffective. This means that the receipt of parking fees on the edge of public roads is categorized as ineffective because it is far from the predetermined target.